Long-term residual effects of biochar from tobacco scraps on red spinach (Amaranthus tricolor) growth in Entisols: a five-year field experiment with urea fertilizer addition - Agabus Ary Koreh; Widowati; Reza Prokoso Dwi Julianto (Jurnal Ilmiah Pertanian, 2023)
The residual effects of biochar doses on Entisols after five years of application have not received attention. However, there is an assumption that the positive effects of biochar can last longer in the soil. Therefore, field experiments were carried out in polybags to assess the residual impact of applying biochar doses in the fifth year and the addition of urea fertilizer on the growth of red spinach (Amaranthus tricolor) in Entisol. The growing media used in this study was a medium previously used for five years containing biochar in Entisols. This study used a 2-factor randomized block design consisting of residual doses of biochar (3 levels) and the addition of urea fertilizer (2 levels). There was no interaction between biochar and N fertilizer. Application of biochar at a dose of 500 g/polybag gave a better follow-up effect than 250 g/polybag on the growth of red spinach in the fifth year. Chlorophyll content increased with N fertilization. Applying biochar in the fifth year and N fertilization positively impacted the growth of red spinach in Entisol. Spinach yield increased 30% at the remaining dose of biochar 500 g/polybag and 52% with N fertilization. Within five years, using higher doses of biochar and adding urea will result in better growth of red spinach in Entisol.